High efficiency solar cell characterization - Goh, Wee Quan (2014)
The study of characterization of solar cell is closely related to the analysis of solar parameters, spectral response and quantum efficiency. Therefore, an accurate and efficient of solar efficiency measurement is highly needed in the current phase of solar technology. The project is conducted in two pipelines. The first pipeline is to develop a spectral response measurement by using electronic-control source. This measurement enables us to measure spectral response of solar cell sample at the wavelength at 460nm, 850nm and 940nm. The second pipeline is to analysis the solar cell samples, which are developed by Nanyang Technology University Characterization Lab. These samples are measured by the developed spectral response measurement, one sun measurement and quantum efficiency measurement. With the above analyses, the future enhancement of the solar cell can thus be examined through the study of this project. This project also discovered the limitations of the developed spectral response measurement by making valuable recommendations. Lastly, this project can serve as a guideline for further development of spectra response measurement and to study the characteristic of solar cell.